A new species of Placusa Erichson (Coleoptera, Staphylinidae, Aleocharinae) from China - Gao, Jiangyong; Ji, Baozhong; Liu, Shuwen (Zootaxa, 2011)
A new species, Placusa pinearum Gao, Ji, Liu, sp. nov. from China, is described and illustrated. The line drawings of aedeagus, spermatheca and scanning electron micrographs of different parts of mouthparts and body are provided.